Sistematized search of plants with pharmacolo gic activity using Bank of plants extracts of native and naturalized plants of La Pampa province (Veterinary Science, 2017)
Bank of plants extracts(BEV) has been created with the purpose of use the collected extracts to evaluate the pharmacological potential of plants using experimental models /in vitro/ and /in vivo/. BEV is an extract collection obtained from aerial parts of native and naturalized plants of La Pampa province. Extracts are obtained at room temperature using ethanol:water (1/1, v/v) as a solvent, desiccated by low pressure and storage at -20ºC. Samples ready to use in bioassays availability makes possible randomly search to detect pharmacological activity. By this procedure was possible to determinate antimicrobial, antispasmodic, gastro protective and anti-inflammatory activities in different plant species. The presence of these properties was confirmed in some cases, and in other these properties, without backgroun etnopharmacological information, were determin ed. Systematic studies carried out using the BEV resources are used to extend knowledge and possibly use the pharmaco-botanical potential of plants that growth in La Pampa provincia
Keywords: Bank of plants extracts; Pharmacobot anic; Pharmacognosy